2012
DOI: 10.5194/amt-5-1925-2012
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a low-cost methane sensor for ambient concentration measurements in preliminary studies

Abstract: Abstract. Methane is the second most important greenhouse gas after CO 2 and contributes to global warming. Its sources are not uniformly distributed across terrestrial and aquatic ecosystems, and most of the methane flux is expected to stem from hotspots which often occupy a very small fraction of the total landscape area. Continuous time-series measurements of CH 4 concentrations can help identify and locate these methane hotspots. Newer, low-cost trace gas sensors such as the Figaro TGS 2600 can detect CH 4… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 35 publications
4
107
0
Order By: Relevance
“…Interference by water vapour and T has been previously shown (Pavelko, 2012;van den Bossche et al, 2017). RL is therefore ideally determined in dry air containing no volatile organic compounds or other reduced gases at a standard T. However, it can be challenging to determine RL, and Eugster and Kling (2012) proposed to use the lowest measured sensor output voltage (V0), representing minimum background atmospheric levels, to determine an empirical 110 reference resistance R0, and to calculate the ratio of RS/R0, reflecting the relative sensor response as follows:…”
Section: Data Processing and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interference by water vapour and T has been previously shown (Pavelko, 2012;van den Bossche et al, 2017). RL is therefore ideally determined in dry air containing no volatile organic compounds or other reduced gases at a standard T. However, it can be challenging to determine RL, and Eugster and Kling (2012) proposed to use the lowest measured sensor output voltage (V0), representing minimum background atmospheric levels, to determine an empirical 110 reference resistance R0, and to calculate the ratio of RS/R0, reflecting the relative sensor response as follows:…”
Section: Data Processing and Interpretationmentioning
confidence: 99%
“…This approach allows sensor use without accurate specific determination of RL. Previous attempts to calibrate these type of 115 sensors for environmentally relevant applications have focused on CH4 levels of 2-9 ppm, and typically considered the influence of T and RH or H (Casey et al, 2019;van den Bossche et al, 2017;Collier-Oxandale et al, 2018;Eugster and Kling, 2012). In these cases, an approximately linear response of the relative sensor response could be assumed due to the narrow CH4 range.…”
Section: Data Processing and Interpretationmentioning
confidence: 99%
“…Spatial methane distribution data that can be used to identify source pathways is currently still very rare and traditionally its monitoring has been reserved to large institutions capable of absorbing the associated high costs. Compared to previous efforts that collected spatial methane data in the Arctic by helicopter [41,42], by small aircraft [10], by ground based laser scanning [43], or with a ground based solid-state trace gas sensor [44] the methodology presented herein exemplifies a significantly more affordable (< $2500) and more flexible method towards acquiring spatial methane distributions. With the rapid commercial spread of UAVs the presented UAS system has the potential to accelerate the availability of high resolution spatial methane data through university and citizens science and thus gain significantly better insights into methane pathways and its related processes.…”
Section: Resultsmentioning
confidence: 99%
“…Low-cost, off-the-shelf, metal oxide-based methane (CH 4 ) gas sensors have also been tested for monitoring methane leaks. They gave quite reliable data in laboratory conditions when properly correcting for the influence of air temperature and relative humidity [25], as well as in the field for recording ambient concentrations [26]. Dyakowska and Pęgielska [27] tested trained operators using the EN 15446 and the Hi Flow sampler technique and found that the Hi Flow sampler gave the best results.…”
Section: Leak Rate Quantificationmentioning
confidence: 99%